The impact of immune checkpoint inhibitors on prognosis in unresectable hepatocellular carcinoma treated with TACE and lenvatinib: a meta-analysis - Zhang, Wei; Liu, Zirong; Liu, Hongjin; Huang, Zhangkan; Huang, Xiaozhun; Xu, Lin; Che, Xu; Zhan, Zhengyin (Frontiers in Immunology, 2025)
BackgroundCombination of multiple therapies is a common approach to treating patients with unresectable hepatocellular carcinoma (uHCC). The impact of immune checkpoint inhibitors (ICIs) on prognosis in uHCC patients treated with transarterial chemoembolization (TACE) and lenvatinib remains unclear.AimThe purpose of this study was to compare the efficacy and safety of TACE plus lenvatinib plus ICIs (TACE+L+I) with TACE plus lenvatinib (TACE+L) in the treatment of patients with uHCC.MethodsPublicly available studies comparing the efficacy and safety of TACE+L+I and TACE+L in the treatment of uHCC were collected from the databases PubMed, Embase and Cochrane Library, with a cut-off date of November 1, 2024. Stata SE 15 software was used for analysis.ResultsFifteen studies with a total of 1365 patients were included, 688 in the TACE+L+I group and 677 in the TACE+L group. Meta-analysis showed that the TACE+L+I group was significantly higher than the TACE+L group in complete response (RR = 2.34, 95%CI:1.53, 3.59, p < 0.0001), partial response (RR = 1.45, 95%CI:1.28, 1.64, p < 0.0001), objective response rate (RR = 1.55, 95%CI:1.39, 1.73, p < 0.00001), and disease control rate (RR = 1.22, 95%CI:1.10, 1.36, p = 0.0003). The TACE+L+I group was significantly lower than the TACE+L group in progression of disease (RR = 0.39, 95%CI:0.30, 0.51, p < 0.00001). Moreover, TACE+L+I group was not significantly different from TACE+L group in stable disease (RR = 0.85, 95%CI:0.69, 1.03, p = 0.10). The TACE+L+I group was significantly higher than the TACE+L group in overall survival (HR = 2.32, 95%CI:1.95, 3.15, p<0.05) and progression-free survival (HR = 2.30, 95%CI:1.80, 2.93, p<0.05). The TACE+L+I group had a significantly higher incidence of hypothyroidism compared to the TACE+L group (RR = 1.81, 95%CI:1.20, 2.71, p<0.05), but there was no significant difference in other adverse events, such as hypertension, diarrhea, hand-foot syndrome, fatigue, elevated AST, elevated ALT, decreased appetite, hypothyroidism, abdominal pain, thrombocytopenia, rash, and nausea.ConclusionICIs significantly improved the survival outcome of uHCC treated with TACE+L, and increased the incidence of hypothyroidism. However, this conclusion still needs further validation in the future with more high-quality randomized controlled trials and longer follow-up.